Puncturing lipid membranes: onset of pore formation and the role of hydrogen bonding in the presence of flavonoids - Sadžak, Anja; Brkljača, Zlatko; Eraković, Mihael; Kriechbaum, Manfred; Maltar-Strmečki, Nadica; Přibyl, Jan; Šegota, Suzana (Journal of lipid research, 2023)
Products of lipid peroxidation induce detrimental structural changes in cell membranes, such as the formation of water pores, which occur in the presence of lipids with partially oxidized chains. However, the influence of another class of products, dicarboxylic acids, is still unclear. These products have greater mobility in the lipid bilayer, which enables their aggregation and the formation of favorable sites for the appearance of pores. Therefore, dodecanedioic acid (DDA) was selected as a model product. Additionally, the influence of several structurally different flavonoids on DDA aggregation via formation of hydrogen bonds with carboxyl groups was investigated. The molecular dynamics of DDA in DOPC lipid bilayer revealed the formation of aggregates extending over the hydrophobic region of the bilayer and increasing its polarity. Consequently, water penetration and the appearance of water wires was observed, representing a new step in the mechanism of pore formation. Furthermore, DDA molecules were found to interact with lipid polar groups, causing them to be buried in the bilayer. The addition of flavonoids to the system disrupted aggregate formation, resulting in the displacement of DDA molecules from the center of the bilayer. The placement of DDA and flavonoids in the lipid bilayer was confirmed by small-angle X-ray scattering. Atomic force microscopy and electron paramagnetic resonance were used to characterize the structural properties. The presence of DDA increased bilayer roughness and decreased the ordering of lipid chains, confirming its detrimental effects on the membrane surface, while flavonoids were found to reduce or reverse these changes.
Keywords: physical biochemistry; dicarboxylic acid; lipid/peroxidation; phospholipid/phosphatidylcholine; flavonol; oxidized lipid; flavone; antioxidant